Portraying Homosexuality in Hollywood: The Case of The Children’s Hour and Carol - Casanova, Fábio (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2022)
This essay seeks to analyse the depiction of homosexuality in the films The Children’s Hour (1961) and Carol (2015). For that purpose, we start by considering the main plot points of each film. Then we move into an overview of the cultural and social background of each work. In the case of The Children’s Hour, we discuss the relationship between this and other Hollywood films from that time with the same subject. We also take into consideration the reception of the homonymous play by Lillian Hellman that inspired this film. As far as Carol is concerned, we delve into the social circuit of Patricia Highsmith (the author of the novel on which Carol is based): 1950s New York. As a result, we realise the importance of such a novel being published in 1952, as well as a possible reason why it was just now made into a film. Finally, we compare how both films portray homosexuality and lesbian love stories, relating their differences to each film’s historical background.